2014
DOI: 10.1177/0002764214550288
|View full text |Cite
|
Sign up to set email alerts
|

Becoming DACAmented

Abstract: In response to political pressure, President Obama authorized the Deferred Action for Childhood Arrivals (DACA) program in 2012, giving qualified undocumented young people access to relief from deportation, renewable work permits, and temporary Social Security numbers. This policy opened up access to new jobs, higher earnings, driver's licenses, health care, and banking. Using data from a national sample of DACA beneficiaries (N = 2,381), this article investigates variations in how undocumented young adults be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(66 citation statements)
references
References 44 publications
(69 reference statements)
1
65
0
Order By: Relevance
“…Importantly, DACA improved employment opportunities for some undocumented youth (Gonzales, Terriquez, and Ruszczyk 2014), while the California DREAM Act made college more affordable for undocumented students. Together, this federal directive and state legislation likely facilitate continuous enrolment, and consequently degree completion, among these immigrant students.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, DACA improved employment opportunities for some undocumented youth (Gonzales, Terriquez, and Ruszczyk 2014), while the California DREAM Act made college more affordable for undocumented students. Together, this federal directive and state legislation likely facilitate continuous enrolment, and consequently degree completion, among these immigrant students.…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 200,000 children had parents who were eligible for DACA at the time the policy was announced (2). Although some studies have found that DACA recipients have higher rates of employment (2022) and improved health outcomes (23, 24), the intergenerational effects of DACA are largely unknown.…”
mentioning
confidence: 99%
“…Every nine out of 10 respondents of the NURP study reported receiving assistance with their DACA application from community organizations, professional attorneys, and individuals within their network. 50 Elaborating on credible sources of support can reduce fraud and scamming by notarios. Interested individuals, eligible or ineligible, can be informed on how to become leaders, activists, and supporters of the legalization of others to strengthen trust in the program.…”
Section: Community Education and Outreachmentioning
confidence: 99%
“…NURP researchers found that those who were most engaged with civic organizations were most likely to apply for and successfully obtain DACA. 52 Having already developed ties to immigrant communities, organizations can better cater outreach efforts in the wake of a new legalization program.…”
mentioning
confidence: 99%